Fluorpen a simple hand held chlorophyll fluorescence measuring instrument - Zabkiewicz, J.A.; Horgan, D.B. (New Zealand Plant Protection, 2008)
Plant chlorophyll fluorescence (CF) can be determined in a number of ways from spot readings or whole leaf scans Whole plant numerical and false colour CF analyses under laboratory conditions are now common but this is not an approach that can be easily applied under field conditions A portable hand held CF measuring instrument now provides a simple and rapid means of obtaining appropriate CF ratios for plants under laboratory or field conditions The Fluorpen can rapidly measure quantum yield fluorescence decline nonphotosynthetic quenching and OJIP CF ratios The unit can store many determinations which can then be easily downloaded into a computer via a Bluetooth link to access results rapidly unlike the bench top instrument which requires considerable time for image and data processing after capture Examples will be given of the different outputs and operational requirements for a typical application using plants that have been treated with agrichemicals Different versions of the unit can also be used to monitor the CF characteristics of fruit or to measure concentrations of photosynthetic algae in water